Quality and bioactive compound accumulation in two holy basil cultivars as affected by microwave-assisted hot air drying at an industrial scale - Wiset, Lamul; Poomsa-ad, Nattapol; Jindamol, Hathairut; Thongtip, Akira; Mosaleeyanon, Kriengkrai; Toojinda, Theerayut; Darwell, Clive Terence; Saputro, Triono Bagus; Chutimanukul, Panita (Frontiers in Sustainable Food Systems, 2023)
Holy basil (Ocimum Tenuiflorum L.) contains several bioactive compounds useful to the pharmaceutical and food industries. Microwave drying (MD) is a powerful technique for rapid drying of food or plant materials while preserving bioactive compounds during the process. However, little is known about the optimal combination of MD power with hot air drying (HAD) can be preserved quality and provide reasonable energy consumption in dried holy basils. For that purpose,We therefore examined the effects of drying methods, using MD combined with hot air dryingHAD at 45 Running Title °C (HAD)were examined to prevent the losses in quality, antioxidant activities and volatile flavor compounds in two holy basil cultivars (green and red cultivars). Holy basil leaves were dried at different MD powers of 200, 400 and 600 W combined with HAD and compared with a traditional tray drying (TD) at 45°C. Drying using MD at 600 W with HAD displayed significantly highest levels of color retention, and chlorophyll and carotenoid content in both of cultivars. However, the green cultivar showed a greater accumulation in total phenolic compounds (TPC), terpenoids and DPPH free radical scavenging at 400 W with HAD. For the red cultivar, the highest TPC, flavonoid and terpenoids content were found at 600 W with HAD. The accumulation of major volatile organic compounds (VOCs) was also affected, treatment at 600 W exhibited the highest Methyl eugenol and β-caryophyllene content in both cultivars. Moreover, the use of the highest power of MD (600 W) with HAD for leaf drying reduced effective drying time and energy consumption among both cultivars, considering both dried quality of antioxidant accumulation and energy consumption, drying using MD power with HAD at 400 or 600 W for the green cultivar, and 600 W for red, are recommended.